EFFECTIVENESS OF CERTIFIED INDEPENDENT STUDY IMPLEMENTATION FOR STUDENTS OF INFORMATICS AND COMPUTER ENGINEERING DEPARTMENT - Muhammad Fadhil Firdaus; Mustari Lamada; Fathahillah Fathahillah (Lembaga Penelitian Mahasiswa Penalaran UNM, 2023)
This research is a review to measure the level of feasibility to assess the implementation of the Certified Independent Study program for students of the Department of Informatics and Computer Engineering, Makassar State University using four points of view, namely functions, programs, goals and ideal conditions. The subjects in this study were 29 students majoring in Informatics and Computer Engineering who had attended the Certified Independent Study program. The research method used was quantitative descriptive, and samples were taken using total sampling where the sample size is equivalent to the population because the population size is very less or below 100. Data collection was conducted through a survey in the form of Google form questionnaire. Descriptive statistics were used in the analysis of this research data which are presented in tabular form. Based on the measurement of the four main aspects, the level of effectiveness of Certified Independent Study programs run by students majoring in Information and Computer Engineering can be concluded to be in the medium category. The obstacles faced by students include difficulties in understanding the material, network problems, software performance issues, lack of learning media support, hardware problems, less effective time management, lack of communication with mentors, overlapping activities, lack of cooperation in groups, time-consuming examination process, and problems in the process of recognition